Billions. Season five [videorecording (DVD)] - Koppelman, Brian; Levien, David; Sorkin, Andrew Ross (Paramount Home Entertainment, 2022)
Bobby Axelrod and Chuck Rhoades see their vicious rivalry reignited, while new enemies rise and take aim. Social impact pioneer Mike Prince poses a true threat to Axe's dominance, and Chuck feuds with a formidable district attorney. Taylor Mason is forced back to Axe Capital, where Taylor must fight to protect their employees and their assets. Wendy Rhoades reevaluates her loyalties and forges surprising new alliances that put her at odds with both Chuck and Axe.